Experimental Evaluation of the Influence of Early Disturbance on the Performance of Basalt Fiber Concrete - Zhe Huang; Yan Li; Yichen Liu; Fengjie Cai; Tianyu Liang (Advances in Civil Engineering)
By applying early disturbance to the concrete, the influence of the disturbance on the macroscopic mechanical properties of basalt fiber concrete during the period from the initial setting to the final setting is explored, and the influence mechanism is revealed. Also, the influence of this disturbance on the process of sulfate erosion of concrete is evaluated by the sulfate erosion test and by the ultrasonic data acquisition of its damage process. The experimental results show that the flexural strength of basalt fiber concrete is increased after the concrete has been disturbed in the early stage of condensation but is decreased in the middle stage of condensation and is not affected in the later stage. When the condensation and hardening processes are disturbed, damage is caused inside the concrete, which is greater with the increase in the condensation degree until the penetration resistance reaches about 15 MPa, which then is more and more reduced. The durability of basalt fiber concrete is reduced by disturbance, which has a significant effect on it when the penetration resistance is between 7 MPa and 16 MPa.